Pointing and the interference effect in obsessive‐compulsive disorder (OCD). Issue 3 (11th March 2013) - Dittrich, Winand H.; Johansen, Thomas; Trotter, Kayleigh; Dawes, Helen; Kischka, Udo
<x xml:space="preserve">Abstract</x> The interference effect in obsessive‐compulsive disorder (OCD) was investigated in order to analyze cognitive aspects of motor stereotypy in OCD‐related compulsions. So far, the domain of cognitive control in compulsive behavior has been under‐investigated. Twelve participants (OCD patients and healthy controls) completed a newly created computer‐based pointing task as well as standard clinical and psychological background measures. Findings showed that the patients displayed a larger visual interference effect compared to the controls and pointing paths were longer in time as well as distance when a distractor stimulus was present. It is concluded that, for compensation, patients would need to generate excessive amounts of attentional resources not available to overcome motor rigidity on the one side and visual distraction on the other side.